Economic analysis for management decisions - Elliott, Jan Walter (Homewood, Ill. : R. D. Irwin, 1973)
The book is divided into three parts: Part I. Tools for Measuring Economic Relationships. Part II. Analysis of Demand, Cost, and Market Prices. Part III. Analyzing Economic Behavior of Firms.
Includes bibliographical references.
rpm 01/02/2019
Loans
Keywords: Microeconomics; Econometrics; Managerial economics